The Effect of Concurrent Motor Activity on the Perception of Biological Motion - Ohson, Singh Simran (My University, 2012)
Recent efforts to explain the underlying mechanisms of action observation have resulted in several theoretical frameworks. The Common Coding framework proposes that the perception and action areas of the brain share representations of visual and motor feedback such that areas are activated concurrently, there is a benefit to an individual’s perceptual ability and confidence. The MOSAIC framework, on the other hand, proposes that these benefits derive from self generations of motor commands during voluntary movement. This study aimed to observe the effects of concurrent motor activity on perceptual ability and judgments of performance. Participants observed an animated avatar performing pairs of symbol tracings on a screen. Participants were also placed into one of three concurrent movement groups: voluntary concurrent symbol tracing, non-voluntary concurrent symbol tracing or observation (no concurrent symbol tracing). It was expected that the group with voluntary concurrent movement would exhibit a higher perceptual accuracy and greater ability to judge performance than both the non-voluntary concurrent movement group and the observation group. However, all participants demonstrated the same level of perceptual accuracy, regardless of the level of concurrent movement. The decreased ability for voluntary movement participants was likely due to significant movement initiation time delays associated with cognitive processing of visual stimuli. As such, voluntary participants did not move in synchrony with the display. Nevertheless, both movement groups had a greater ability of judging performance, suggesting that judgments of performance may be obtained using different pathways than those involved in perceptual accuracy. Findings support both the Common Coding and MOSAIC frameworks, suggesting that a perceptual benefit can only be obtained when movement is in synchrony with perception.
Keywords: Action Observation; Concurrent Movement; MOSAIC; Perception; Biological Motion; Cognition and Perception; Cognition and Perception